Perbedaan Hasil Belajar Matematika Siswa ditinjau dari Level Geometri Van Hiele SMP Kelas VII - Anwar, Azwar (FKIP Universitas Mataram, 2019)
This study aims to determine the distribution of student geometry levels based on Van Hiele's theory and find out the differences in students' mathematics learning outcomes in grade VII junior high school. The sampling technique is probability sampling and a sample of 182 students is obtained. Data collection techniques used were Van Hiele level geometry tests and test results. Data analysis used descriptive statistics and anova with a significance level of 5%. The results showed that only 170 students were included in the Van Hiele geometry level, namely 62 students were at level 0, 97 students were at level 1, 5 students were at level 2, and as many as 6 students are at level 3. In the inferential analysis based on analysis of variance (two-way anova) concludes that for learning outcomes based on Van Hiele level geometry obtained Fcount = 13.793 > Ftable = 9.28 means H0ÃƒÂ‚Ã‚Â is rejected means that there are differences in mathematics learning outcomes based on Van Hiele geometry level.AbstrakPenelitian ini bertujuan untuk mengetahui distribusi level geometri siswa berdasarkan teori Van Hiele dan mengetahui perbedaan hasil belajar matematika siswa di kelas VII SMP. Menggunakan teknik probability sampling dan diperoleh sampel sebanyak 182 siswa. Teknik pengumpulan data yang digunakan adalah tes level geometri Van Hiele dan tes hasil belajar. Analisis data menggunakan statistik deskriptif dan anova dengan taraf signifikansi sebesar 5%. Hasil analisis data menunjukkan bahwa dari 182 sampel, hanya 170 siswa yang termasuk dalam level geometri Van Hiele yaitu 62 siswa berada pada level 0, sebanyak 97 siswa pada level 1, sebanyak 5 siswa pada level 2, dan ÃƒÂ‚Ã‚Â 6 siswa pada level 3. Analisis anova dua arah diperoleh Fhitung = 13,793 > Ftabel = 9,28 berarti H0ÃƒÂ‚Ã‚Â ditolak yang artinya terdapat perbedaan hasil belajar matematika berdasarkan level geometri Van Hiele.